MENGHITUNG KEHILANGAN HASIL KOMODITAS KEDELAI - Harimurti, Monica; Priyanto, Eko (Berkala Ilmiah AGRIDEVINA, 2021)
The purpose of this research is to analyze the amount and value of soybean commodity yield losses, and recommend strategic efforts and actions that should be taken to reduce yield losses. The study was conducted in Puter Village, Kembangbahu Subdistrict, Lamongan Regency in March 2020. Researchers used 15 respondents who could represent the population of soybean farmers in Puter Village as many as 122 farmers, for each stage of soybean yield loss calculation. The analysis used is the calculation of the estimated amount and value of yield loss. The results of this study indicate that the cumulative loss of soybean commodity in Puter Village is 13.13% which occurs in the stages of harvesting, drying of stover, gathering, threshing and drying of soybean seeds. Loss of storage results cannot be calculated because farmers in Puter Village sell their soybean directly after drying. The cause of this loss in soybean yields is caused by improper handling of crops and postharvest both the method and technology used. DOI : https://doi.org/10.33005/adv.v10i1.2616